Prevalence of concomitant pulmonary tuberculosis in patients with newly diagnosed silicosis in a tertiary care center in South India - Navaneethakrishnan Muthulakshmi ,; Saravanavasan Rajendran,; Kannan Muthuraman Alagappan, (Asian Journal of Medical Sciences, 2023)
Background: Long-term exposure to silica dust makes people prone for silicosis which raises the risk of the individual in developing pulmonary tuberculosis (PTB). Silicosis is a progressive lung disease characterize with shortness of breath, cough, fever, and bluish skin, caused due to inhalation of crystalline silica dust found in abundance in sand, rock, and quartz. Aims and Objectives: The disease is known to effect the functioning of macrophages making it unable to defend mycobacterium species, thus allowing the bacterium to invade and develop tuberculosis. Materials and Methods: A retrospective cross-sectional study is carried out to estimate the prevalence of PTB in newly diagnosed silicosis patients at Madurai Medical College, Madurai, Tamil Nadu. All the patients who got registered in Occupational Lung Diseases Registry from January 2016 to December 2021 are included in the study. Silicosis patients tested positive on sputum CBNAAT are considered as silicotubercular patients, whose prevalence is calculated. Results: Our study included a total of 54 subjects (90.8% males and 8.2% female) with mean SD age of 38±6.7 years ranging from 26 to 53 years. Of which 22 patients, 40.7% tested positive for Mycobacterium tuberculosis (MTB) on sputum CBNAAT. The prevalence of MTB in among silicosis patients was found to be 40.7%. Conclusions: Association of TB and silicosis is very strong with the prevalence of TB among silicosis patients as 40.7%. Our study also observed the male sex and elder age as elevated risk of developing silicotuberculosis. All the people getting exposed to silica dust need to be educated in the usage and usefulness of protective equipment.